Properties of furfurylated wood (Pinus pinaster) - Esteves, Bruno (2021)
Abstract Sapwood samples of Pinus pinaster wood were treated with a 70% furfuryl alcohol mixture. Weight percent gain (WPG), equilibrium moisture content, dimensional sta- bility, MOE, bending strength, hardness, density and dura- bility were determined. WPG was on average 38%. Equilibrium moisture con- tent decreased more than 40%. Dimensional stability in- creased reaching an ASE of 45%. MOE was little affected by the treatment but bending strength increased by about 6%. Hardness increased by about 50%, and density by 37%. Mass loss due to Postia placenta and Coniophora puteana decreased by 96% and 86%, respectively. Furfurylation of Pinus pinaster wood shows an interesting potential to im- prove the wood quality for solid timber products.